Applications of variational iteration and homotopy perturbation methods to fractional evolution equations - Odibat, Zaid; Momani, Shaher (Topological Methods in Nonlinear Analysis, 2008)
In this paper, variational iteration and homotopyperturbation methods that developed for integer-order differentialequations are directly extended to derive explicit and numericalsolutions of various evolution equations with time-fractionalderivatives. The results reveal that the two methods are veryeffective and convenient for solving nonlinear partial differential equations of fractionalorder.